An Integrative Approach: Relational Cultural Theory and Cognitive Behavior Therapy in College Counseling. Issue 3 (5th October 2017) - Crumb, Loni; Haskins, Natoya
Abstract : This article presents an integrative framework for using cognitive behavior therapy through the lens of relational cultural theory. The authors provide an overview of cognitive behavior therapy and relational cultural theory, followed by suggestions on how to facilitate cognitive behavior therapy using the principles of relational cultural theory in college counseling. A case illustration is used to demonstrate the integration of cognitive behavior therapy and relational cultural theory.